The Influence of Dividend Policy on The Value of Textile and Garment Manufacturing Companies Listed on The Indonesian Stock Exchange (IDX) For The Period 2022-2024 - Rea, Irena; Maria; Muni, Wihelmina (CV. Jala Berkat Abadi, 2025)
This research examines the influence of dividend policy on firm value in the textile and garment sub-sector of the manufacturing industry listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. The background is increasingly fierce global competition, where company value becomes an indicator of performance and investor appeal. Dividend policy, as the distribution of profits to shareholders, serves as a positive signal that influences market perception of company value. The research method is quantitative, using secondary data from annual financial statements. The analysis was conducted using simple linear regression, where the Dividend Payout Ratio (DPR) served as the independent variable and Price to Book Value (PBV) as the dependent variable. The results show a positive and significant influence of dividend policy on firm value, with a coefficient of determination (R²) of 0.907. This means that 90.7% of the variation in firm value is explained by dividend policy, while 9.3% is influenced by other factors such as profitability, financing policy, firm size, and economic conditions. In conclusion, higher dividend payments increase investor confidence and drive up company value. The recommendation for the company is to maintain a consistent and transparent dividend policy. For investors, dividends can be a key investment benchmark, considering other fundamental factors.